Posterior Reversible Encephalopathy Syndrome Developing after Aggressive Posterior Fossa Tumor Surgery - Bozkurt, Gokhan; Mammadkhanli, Orkhan; Ozden, Mahmut (Asian Journal of Neurosurgery, 2022)
Posterior reversible encephalopathy syndrome (PRES) is a rare neurologic disorder, having such common radiological findings as vasogenic edema and white matter changes in watershed areas. The clinic and radiological outcome may not be reversible in 10 to 20% of patients, like in the case of our patient. Here, we discuss the pathogenetic factors that are essential in developing PRES after posterior fossa surgery. A 4-year-old female was admitted to our clinic with a recurrent/residual mass in the posterior fossa. She previously underwent posterior fossa surgery three times (for what was diagnosed as anaplastic astrocytoma through pathohistology) in another center. She was operated thrice in 5 days, and the tumor radically removed. Two days later, after the last surgery, while waking up, our patient developed seizures and altered consciousness. Her neurological condition was severe. Magnetic resonance imaging findings were compatible with those of PRES. Our patient had multiple risk factors for PRES that were as follows: multiple posterior fossa surgeries, anamnesis of chemotherapy and radiotherapy, high-dose steroid use, intracranial pressure changes, and hypertensive attacks due to surgical manipulation. In preventing the development of PRES, we should beware of sudden changes in blood pressure during surgery and meticulously manipulate the brain stem to avoid any disturbance of the central nervous system homeostasis. PRES may transform into real encephalopathy. If the patient has some of these risk factors, PRES would probably develop after surgery.
Keywords: anaplastic ependymoma; brain stem compression; posterior fossa surgery; posterior reversible encephalopathy syndrome (PRES)